Calcium antagonist nifedipine in treating pregnant women with arterial hypertension: pro and contra - N. K. Runikhina; B. Ya. Bart; O. N. Tkacheva (Кардиоваскулярная терапия и профилактика)
Calcium antagonist nifedipine, an antihypertensive and anti-anginal medication with vasodilating action, is widely used in cardiology practice. According to the recommendations on cardiovascular disease management in pregnancy, by the European Society of Cardiology (2003) and Society of Cardiology of the Russian Federation (2003), nifedipine could be used for hypertension treatment in pregnancy. Positive experience of nifedipine use as an antihypertensive and tocolytic agent has been obtained. The medication has been proved as safe in III pregnancy trimester; its teratogenic and embryotoxic effects in the first pregnancy half have not been confirmed in clinical practice. Oral nifedipine effectively reduces increased blood pressure (BP) in hypertensive crises. Regular nifedipine therapy in pregnancy-associated hypertension facilitates effective BP control and prevents hypertensive crises.